2010
DOI: 10.1124/dmd.110.032862
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Uptake of the Magnetic Resonance Imaging Contrast Agent Gd-EOB-DTPA: Role of Human Organic Anion Transporters

Abstract: ABSTRACT:Contrast-enhancing magnetic resonance imaging with the liverspecific agent gadolinium-ethoxybenzyl-diethylenetriamine pentaacetic acid (Gd-EOB-DTPA) has been shown to improve the detection rate of focal lesions. There is evidence from preclinical studies that multidrug organic anion transporters are involved in hepatic uptake of Gd-EOB-DTPA. Therefore, we evaluated affinity of the contrast agent to human organic anion-transporting polypeptides (OATP1B1, OATP1B3, OATP2B1) and to the Na The uptake by OA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
193
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 211 publications
(200 citation statements)
references
References 27 publications
(28 reference statements)
6
193
1
Order By: Relevance
“…The observed relationship between R 1 and induction of Oatp1 expression indicates that the kinetics of contrast agent uptake should give quantitative estimates of gene expression levels. Finally, because Gd 3+ -based hepatocyte-specific contrast agents have been approved for human use (15), and human OATP1B3 has been shown to take up this contrast agent (16), this could facilitate transfer of this technology to the clinic in the longer term.…”
Section: Discussionmentioning
confidence: 99%
“…The observed relationship between R 1 and induction of Oatp1 expression indicates that the kinetics of contrast agent uptake should give quantitative estimates of gene expression levels. Finally, because Gd 3+ -based hepatocyte-specific contrast agents have been approved for human use (15), and human OATP1B3 has been shown to take up this contrast agent (16), this could facilitate transfer of this technology to the clinic in the longer term.…”
Section: Discussionmentioning
confidence: 99%
“…51 Therefore, uptake of Gd-BOPTA and Gd-EOB-DTPA could be inhibited by an increase in serum bilirubin levels and by inhibitors such as bromosulfophthalein and rifampicin. 52,53 In contrast, the gadolinium-labeled HDL nanoparticles we developed were taken up via HDL-receptor mediated pathways, which were not easily blocked and might more efficiently increase the contrast of the liver parenchyma. More importantly, we showed that gadolinium complexes could participate in the hepatic cholesterol metabolic pathway and be excreted into the bile, which could be of great benefit for assessing the anatomic structure and functions of the biliary tree.…”
Section: Discussionmentioning
confidence: 99%
“…Hepatocellular uptake of gadoxetate from blood is mediated in humans by the sinusoidal solute carriers OATP1B1, OATP1B3, and NTCP [119]. Its active secretion into bile in rats is via the apical transporter Mrp2 [120] and it is presumed that the human ortholog (MRP2) mediates its biliary excretion in humans.…”
Section: Current Clinical Use Of Gadoxetate In Liver Disease Diagnosismentioning
confidence: 99%